1984
DOI: 10.1093/oxfordjournals.aje.a113919
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives in the Collection and Analysis of Food Frequency Interview Data

Abstract: In addition to frequency of consumption, a food frequency questionnaire may assess amount consumed, often by using food models, and the stability of diet. A food frequency interview directed at preformed vitamin A and beta-carotene was administered to 130 cases and 309 controls in an ongoing population-based case-control study of lung cancer in New Mexico. The questionnaire measured frequency, amount, and stability of consumption for 55 food items. Different combinations of responses to these three types of qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
2

Year Published

1989
1989
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 0 publications
2
23
0
2
Order By: Relevance
“…It was the first time an FFQ had been administered to this particular age group in India and the response was encouraging. There are a number of studies in the literature from Western countries, mostly epidemiological, in which FFQs have been administered to children 5 . The FFQ allows an assessment of the dietary intake of a large number of children, thus improving the power of the study, and it is relatively inexpensive to administer.…”
Section: Discussionmentioning
confidence: 99%
“…It was the first time an FFQ had been administered to this particular age group in India and the response was encouraging. There are a number of studies in the literature from Western countries, mostly epidemiological, in which FFQs have been administered to children 5 . The FFQ allows an assessment of the dietary intake of a large number of children, thus improving the power of the study, and it is relatively inexpensive to administer.…”
Section: Discussionmentioning
confidence: 99%
“…Although quantitative data on portion size of foods increase accuracy in estimating the intake of specific nutrients (Hankin, 1987). Samet et al (1984) noted that portion-size questions provided little additional information in ranking individuals . Humble et al (1987) reported that vitamin A intake calculated with and without portion sizes was similarly related to a reduced risk of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies reported the benefits of using photographs to help individuals in estimating portion size (Morgan et al, 1982;Rutishauser, 1982;Chu et al, 1984;Guthrie, 1984;Samet et al, 1984;Byers et al, 1985;Pietinen et al, 1988a, b;Edington et al, 1989;Lee & Cunningham, 1990;Hankin et al, 1991;Tjonneland et al, 1991;Faggiano et al, 1992). Guthrie (1984) reported that between 14 and 67% of assessments of food portion size were in error by more than 50% when no aid was used.…”
Section: Introductionmentioning
confidence: 99%